Strategi Penguatan Manajemen Rantai Pasok Halal di Era Digitalisasi:Pendekatan Sharia Value Chain: Strengthening Strategies for Halal Supply Chain Management in the Digitalization Era: A Sharia Value Chain Approach - Ihwan Wahid Minu; Siradjuddin; Murtiadi Awaluddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to analyze strategies for strengthening halal supply chain management in the digital era using the Sharia Value Chain (SVC) approach. The focus lies on transparency, data integrity, and distribution speed within the context of digital transformation. The research employs a qualitative method with a descriptive-analytical approach based on literature, reinforced by a normative framework through maqāṣid al-sharī‘ah. The findings reveal that key challenges include the lack of integrated digital systems across halal institutions, limited digital literacy among business actors, and weak halal verification across supply chain stages. The SVC provides a strategic solution by embedding values of honesty, responsibility, and sustainability through the implementation of maqāṣid principles such as hifẓ al-dīn and hifẓ al-māl. The adoption of technologies such as blockchain, IoT, and cloud computing enhances the transparency and accountability of the halal system. This research contributes to the development of a halal supply chain management model rooted in Islamic values and supports national halal industry policies toward an efficient, ethical, and digital system.